Guide to the JCT standard building contract 2016 : JCT standard building contract with quantities (SBC/Q), JCT standard building contract with approximate quantities (SBC/AQ), JCT standard building contract without quantities (SBC/XQ) - Lupton, Sarah (RIBA Publishing, 2017)
Guide to JCT Standard Building Contract 2016 is a practical guide to the operation and administration of JCT's SBC 2016 suite of building contracts (SBC/Q, SBC/AQ and SBC/XQ). All of the contracts' provisions, procedures and conditions are organised and explained by subject, clearly distinguishing the different obligations due to various parties and the contractual issues arising during the course of a job - all backed up by the latest legislation and case law.